Synthesis of Rigid Rod, Trigonal, and Tetrahedral Nucleobase-Terminated Molecules - Jin, Xiao-Yang; Wu, Chuan-Shuo; Liu, An-Di; Liu, Li; Cheng, Liang (Synthesis, 2021)
An efficient fragment splicing method for the construction of multiple nucleobase-terminated monomers has been developed. Conformationally fixed rod, trigonal planar and tetrahedral thymine and adenine structures were generated in moderate to good yields, which will serve as inspiring examples for exploration of nucleobases as natural hydrogen-bond components in supramolecular chemistry.
Keywords: nucleobases; cross-coupling; alkynes; arylation; dendrimers